Pengaruh penggunaan lagu bahasa inggris berirama lambat terhadap pelafalan bunyi konsonan oleh siswa efl - Negara, Kanza Ayomi (Maliki Interdisciplinary Journal, 2025)
Proper pronunciation is an important aspect of learning English as a foreign language, but students often have difficulty pronouncing certain consonant sounds due to phonetic differences between English and their native language. The selection of interesting learning methods is an effective solution to this problem, one of which is through slow rhythmic English songs. This study aims to determine the effect of using slow rhythmic English songs on the pronunciation of consonant sounds by EFL students. This research uses a literature study method that examines the effectiveness of the method of using slow rhythmic songs which are considered capable of helping students pronounce consonants more precisely and comfortably. The results showed that slow rhythmic songs give students time to listen, imitate and remember pronunciation better, create a relaxed learning atmosphere and increase motivation. Hence, the author recommends slow rhythm songs as an effective and fun method of learning pronunciation.